2009
DOI: 10.1136/thx.2009.118430
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to asthma management guidelines by middle-aged adults with current asthma

Abstract: Background: With the increasing burden of asthma worldwide, much effort has been given to developing and updating management guidelines. Using data from the Tasmanian Longitudinal Health Study (TAHS), the adequacy of asthma management for middle-aged adults with asthma was investigated. Methods: Information about spirometry, medication history and current asthma status was collected by the most recent TAHS when participants were in their mid 40s. Only those who reported ever having asthma were eligible for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 33 publications
4
34
1
3
Order By: Relevance
“…Asthmatic patients characteristically rely on SABA use to relieve their symptoms rather than controller medications to control their disease. Reports from the United States 36 and around the world 37 have consistently described poor adherence with controller medication use by patients with persistent asthma, surprisingly so in patients with difficult-to-treat asthma. 38 Nonadherence to controller medication use in asthmatic patients has been directly related to poor outcomes, such as ED visits and hospitalizations.…”
Section: Discussionmentioning
confidence: 97%
“…Asthmatic patients characteristically rely on SABA use to relieve their symptoms rather than controller medications to control their disease. Reports from the United States 36 and around the world 37 have consistently described poor adherence with controller medication use by patients with persistent asthma, surprisingly so in patients with difficult-to-treat asthma. 38 Nonadherence to controller medication use in asthmatic patients has been directly related to poor outcomes, such as ED visits and hospitalizations.…”
Section: Discussionmentioning
confidence: 97%
“…Although an 80% adherence rate with ICS has been suggested as the minimum acceptable level of adherence for achieving good asthma control [9], reported ICS adherence rates range from 30 to 70% in the literature [10]. A recent longitudinal study of middle-aged adults with asthma found that 74% (n = 351) used inadequate preventer medication [11]. Similarly, in children, inhalers are largely underused; one study in 8-16 year olds found that inhalers were underused on 33% of days in a month [8].…”
Section: Introductionmentioning
confidence: 99%
“…9 One of the plausible reasons for poorly controlled asthma may be that patients with asthma tend to exhibit poor adherence. 10 Poor adherence to controller medication may lead to a decline in lung function, 11 poor symptom control, 12 and increased risk of asthma-related hospitalizations. 13 Furthermore, poorly controlled asthma also places a much larger burden on the national economics compared with guideline-defined well-controlled asthma.…”
Section: Introductionmentioning
confidence: 99%